Electrochemical device and electronic device

By adding a specific proportion of Mn and X elements to the positive electrode active material of the lithium-ion battery and using an electrolyte containing boron lithium salt, the problems of increasing DC impedance and degradation of rate performance of lithium-ion batteries during circulation are solved, and the effect of improving the rate performance and cycle performance of battery is achieved.

CN115066779BActive Publication Date: 2025-02-28NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180013572.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-13
Publication Date
2025-02-28
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

The DC impedance of lithium-ion batteries increases during the cycle, resulting in a decrease in rate performance. The prior art is difficult to effectively reduce the DC impedance growth and improve the rate performance after the cycle.

Method used

A positive electrode active material is used, which contains Mn element and X element (Co or Al element), and the molar ratio of X element and Mn element is between 0.1 and 10. Combined with an electrolyte containing boron lithium salt, the mass ratio of boron lithium salt and the positive electrode active material is regulated.

Benefits of technology

In lithium-ion batteries, the synergistic effect of the positive electrode active material and the electrolyte can simultaneously improve the initial rate performance and cyclic performance, while reducing the DC resistance growth rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003788267500000151
    Figure BDA0003788267500000151
  • Figure BDA0003788267500000161
    Figure BDA0003788267500000161
  • Figure BDA0003788267500000171
    Figure BDA0003788267500000171
Patent Text Reader

Abstract

An electrochemical device and an electronic device, the electrochemical device comprising a positive electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material, the positive electrode active material comprises an Mn element and an X element, the X element comprises at least one of a Co element or an Al element, the molar ratio of the X element to the Mn element is A%, and A is 0.1 to 10; the electrolyte comprises a boron-containing lithium salt. Under the synergistic effect of the positive electrode active material and the electrolyte, the rate performance and cycle performance of the electrochemical device can be improved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemistry, and in particular to an electrochemical device and an electronic device. Background Art

[0002] Lithium-ion batteries are widely used in wearable devices, smart phones, drones, electric vehicles, large energy storage devices and other fields due to their high energy density, long cycle life and no memory effect. They have become the new green chemical power source with the greatest development potential in the world today. However, they also put forward higher requirements on the performance of lithium-ion batteries.

[0003] The effective combination of positive electrode active materials and electrolytes in lithium-ion batteries has a great influence on the performance of lithium-ion batteries. As the number of cycles of lithium-ion batteries increases, the protective film on the surface of the positive and / or negative electrodes is damaged, the DC impedance of the lithium-ion battery increases, and the rate performance of the lithium-ion battery decreases. Therefore, the development of positive electrode active materials and electrolyte systems that are conducive to reducing the growth of DC impedance of lithium-ion batteries and improving the rate performance after cycling has become an urgent problem to be solved. Summary of the invention

[0004] The purpose of the present application is to provide an electrochemical device and an electronic device to improve the rate performance of the electrochemical device.

[0005] The first aspect of the present application provides an electrochemical device, which includes a positive electrode plate and an electrolyte, wherein the positive electrode plate includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes Mn element and X element, X element includes at least one of Co element or Al element, the molar ratio of X element to Mn element is A%, A is 0.1 to 10; the electrolyte includes a boron-containing lithium salt. Under the synergistic effect of the positive electrode active material and the electrolyte, the initial rate performance and cycle performance of the electrochemical device can be improved at the same time, and the DC resistance growth rate can be reduced.

[0006] In some embodiments of the present application, the boron-containing lithium salt comprises at least one of lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium dioxalatoborate or lithium tetraborate.

[0007] In some embodiments of the present application, the mass ratio of the boron-containing lithium salt to the positive electrode active material is 0.0001 to 0.01.

[0008] In some embodiments of the present application, based on the mass of the electrolyte, the mass percentage of the boron-containing lithium salt is 0.01% to 2.2%.

[0009] In some embodiments of the present application, the positive electrode active material includes lithium manganese oxide containing an X element.

[0010] In some embodiments of the present application, the positive electrode active material further comprises an M1 element, and the M1 element comprises at least one of Nb, Mg, Ti, W, Ga, Zr, Y, V, Sr, Mo, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm or Gd, and the molar content a1% of the M1 element is 0.1% to 2% based on the molar number of the Mn element. The inclusion of the above M1 element in the positive electrode active material and the molar content of the M1 element within the above range are conducive to improving the manganese dissolution phenomenon of the positive electrode sheet and improving the cycle performance of the electrochemical device.

[0011] In some embodiments of the present application, the positive electrode active material includes a lithium manganese oxide containing an X element and an M1 element.

[0012] In some embodiments of the present application, the electrochemical device satisfies at least one of the following characteristics: (i) 0.14≤a1 / A≤0.55; (ii) the M1 element includes the Nb element, and the molar content of the Nb element is a2% based on the molar number of the Mn element, satisfying 0.3≤a2 / a1≤1. By regulating the values ​​of a1 / A and / or a2 / a1 within the above range, it is beneficial to improve the cycle performance and initial rate performance of the electrochemical device.

[0013] In some embodiments of the present application, the positive electrode active material further includes an M2 element, the M2 element includes at least one of Fe, Cu, Cr or Zn, and the molar content of the M2 element is b1% based on the molar number of the Mn element.

[0014] In some embodiments of the present application, the positive electrode active material comprises an M1 element and an M2 element, and satisfies 0.1<a1+b1≤2.05. By selecting the above-mentioned M2 element and regulating the value of the total molar content a1+b1 of the Mn element and the M2 element within the above-mentioned range, it is beneficial to improve the cycle performance and initial rate performance of the electrochemical device and reduce the growth rate of the DC resistance.

[0015] In some embodiments of the present application, the positive electrode active material includes lithium manganese oxide containing an X element and an M2 element.

[0016] In some embodiments of the present application, the positive electrode active material includes a lithium manganese oxide containing an X element, an M1 element, and an M2 element.

[0017] In some embodiments of the present application, the positive electrode active material further comprises an M3 element, the M3 element comprises at least one of F, P, S or B, and the molar content c1% of the M3 element is 0.1% to 2% based on the molar number of the Mn element. By selecting the above-mentioned M3 element, controlling the mass ratio of the boron-containing lithium salt to the positive electrode active material to be 0.0001 to 0.01, and regulating the molar content c1% of the M3 element within the above-mentioned range, it is beneficial to form a structurally stable positive electrode active material, form a protective film on the surface of the positive electrode active material, and improve the manganese dissolution phenomenon of the positive electrode sheet, thereby improving the cycle performance of the electrochemical device.

[0018] In some embodiments of the present application, the positive electrode active material includes lithium manganese oxide containing X element and M3 element.

[0019] In some embodiments of the present application, the positive electrode active material includes a lithium manganese oxide containing an X element, an M1 element, and an M3 element.

[0020] In some embodiments of the present application, the positive electrode active material includes lithium manganese oxide containing an X element, an M2 element, and an M3 element.

[0021] In some embodiments of the present application, the positive electrode active material includes a lithium manganese oxide containing an X element, an M1 element, an M2 element, and an M3 element.

[0022] In some embodiments of the present application, the positive electrode active material includes M1 element and M3 element, and satisfies at least one of the following characteristics: (iii) 0.1≤a1+c1≤4; (iv) M3 element includes F element, based on the molar number of Mn element, the molar content of F element is c2%, and 0.05≤c2 / c1≤0.5 is satisfied. By regulating the value of a1+c1 and / or the value of c2 / c1 within the above range, it is beneficial to improve the cycle performance of the electrochemical device.

[0023] In some embodiments of the present application, the positive electrode active material comprises secondary particles, the average particle size of the primary particles in the secondary particles is D1, and the positive electrode active material satisfies at least one of the following characteristics: (1) the Dv50 of the positive electrode active material is 4 μm to 15 μm; (2) the average particle size D1 of the primary particles is 200 nm to 2 μm; (3) 4≤Dv50 / D1≤50, Dv50 is the cumulative particle size of 50% in the volume reference distribution of the positive electrode active material obtained by testing with a laser scattering particle size analyzer. By regulating the values ​​of Dv50, D1 and Dv50 / D1 of the positive electrode active material within the above range, it is beneficial to improve the initial rate performance and cycle performance of the electrochemical device.

[0024] In some embodiments of the present application, the electrolyte further includes a compound containing a sulfur-oxygen double bond, the compound containing a sulfur-oxygen double bond includes at least one of 1,3-propane sultone, propenyl-1,3-sultone or vinyl sulfate, and the mass percentage of the compound containing a sulfur-oxygen double bond is 0.01% to 2% based on the mass of the electrolyte. By selecting the above-mentioned compound containing a sulfur-oxygen double bond and regulating its mass percentage within the above range, the initial rate performance and cycle performance of the electrochemical device are improved, and the DC resistance growth rate can be reduced.

[0025] A second aspect of the present application provides an electronic device comprising the electrochemical device in any embodiment of the present application.

[0026] The first aspect of the present application provides an electrochemical device, which includes a positive electrode sheet and an electrolyte, wherein the positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes Mn element and X element, X element includes at least one of Co element or Al element, the molar ratio of X element to Mn element is A%, A is 0.1 to 10; the electrolyte includes a boron-containing lithium salt, and the mass ratio of the boron-containing lithium salt to the positive electrode active material is 0.0001 to 0.01. Under the synergistic effect of the positive electrode active material and the electrolyte, in the initial stage of charging and discharging of the electrochemical device, it helps to form a protective film on the negative electrode; in the cycle process of the electrochemical device, it helps to repair the protective film of the negative electrode, slow down the increase of the interface impedance of the electrochemical device during the cycle process, so as to improve the problem of the decrease of the rate performance of the electrochemical device during the cycle process; and improve the structural stability of the positive electrode active material, thereby simultaneously improving the initial rate performance and cycle performance of the electrochemical device, and at the same time being able to reduce the DC resistance growth rate. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the following examples are listed to further describe the present application in detail. Obviously, the described examples are only part of the examples of the present application, rather than all of the examples. Based on the examples in the present application, all other examples obtained by ordinary technicians in the field belong to the scope of protection of the present application.

[0028] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.

[0029] A first aspect of the present application provides an electrochemical device, which includes a positive electrode plate and an electrolyte, wherein the positive electrode plate includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes Mn element and X element, the X element includes at least one of Co element or Al element, the molar ratio of X element to Mn element is A%, A is 0.1 to 10, preferably 1 to 5; the electrolyte includes a boron-containing lithium salt.

[0030] In some embodiments of the present application, the boron-containing lithium salt includes at least one of lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB) or lithium tetraborate (Li2B4O7).

[0031] In some embodiments of the present application, the mass ratio of the boron-containing lithium salt to the positive electrode active material is 0.0001 to 0.01. For example, the molar ratio A of the X element to the Mn element can be 0.1, 0.5, 1, 3, 5, 7, 10, or a range consisting of any two values ​​therebetween, and the mass ratio of the boron-containing lithium salt to the positive electrode active material can be 0.0001, 0.001, 0.005, 0.01, or a range consisting of any two values ​​therebetween.

[0032] Without being limited to any theory, the inventors of the present application have found that when the molar ratio of the X element to the Mn element in the positive electrode active material is A%, A is 0.1 to 10, the electrolyte includes a boron-containing lithium salt, and the mass ratio of the boron-containing lithium salt to the positive electrode active material is 0.0001 to 0.01, under the synergistic effect of the positive electrode active material and the electrolyte, in the initial stage of charge and discharge of the electrochemical device, it helps to form a protective film on the negative electrode; during the cycle of the electrochemical device, it helps to repair the protective film and slow down the increase in the interfacial impedance of the electrochemical device during the cycle, thereby improving the problem of decreased rate performance of the electrochemical device during the cycle; and improving the structural stability of the positive electrode active material, thereby simultaneously improving the initial rate performance and cycle performance of the electrochemical device. In electrochemical devices, such as lithium-ion batteries, the mass of boron-containing lithium salts in the electrolyte can be tested by the following method: weigh the lithium-ion battery as m0, disassemble the lithium-ion battery, centrifuge it, soak it in a dimethyl carbonate solution for 10 hours and dry it, weigh it after drying as m1, and the total mass of the electrolyte is m0-m1. The electrolyte obtained by centrifugation is tested by gas chromatography and ion chromatography to obtain the content ratio of each substance in the electrolyte. The mass of boron-containing lithium salt = total mass of electrolyte × content ratio of boron-containing lithium salt.

[0033] In some embodiments of the present application, the positive electrode active material includes at least one of lithium manganese oxide containing an X element or lithium iron manganese phosphate containing an X element.

[0034] In some embodiments of the present application, the positive electrode active material includes lithium manganese oxide containing an X element.

[0035] In some embodiments of the present application, based on the mass of the electrolyte, the mass percentage of the boron-containing lithium salt is 0.01% to 2.2%. For example, the mass percentage of the boron-containing lithium salt can be 0.01%, 0.02%, 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.2%, 1.5%, 2.0%, 2.2% or a range consisting of any two values ​​therebetween. Without being limited to any theory, the inventors of the present application have found that when the content of the boron-containing lithium salt is between 0.01% and 2.2%, especially when the content is between 0.05% and 0.9%, the electrochemical device has better initial rate performance and cycle performance, and the DC impedance growth rate is low.

[0036] In some embodiments of the present application, the positive electrode active material further includes an M1 element, and the M1 element includes at least one of Nb, Mg, Ti, W, Ga, Zr, Y, V, Sr, Mo, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm, or Gd, and the molar content a1% of the M1 element is 0.1% to 2% based on the molar number of the Mn element. For example, the molar content a1% of the M1 element can be 0.1%, 0.5%, 1%, 1.5%, 2%, or a range consisting of any two values ​​therebetween. Without being limited to any theory, the inventors of the present application have found that when the molar content a1% of the M1 element is too low (e.g., less than 0.1%), the performance improvement of the electrochemical device is not obvious; as the molar content a1% of the M1 element increases, under the synergistic effect of the positive electrode active material and the electrolyte, it is conducive to forming a structurally stable protective film to improve the manganese dissolution phenomenon of the positive electrode sheet; when the molar content a1% of the M1 element is too high (e.g., higher than 2%), it affects the initial rate performance and gram capacity of the electrochemical device. The positive electrode active material includes the above-mentioned M1 element and the molar content of the M1 element is within the above-mentioned range, which is conducive to improving the manganese dissolution phenomenon of the positive electrode sheet and improving the cycle performance of the electrochemical device.

[0037] In some embodiments of the present application, the electrochemical device satisfies at least one of the following characteristics: (i) 0.14≤a1 / A≤0.55; (ii) the M1 element includes the Nb element, and the molar content of the Nb element is a2 based on the molar number of the Mn element, satisfying 0.3≤a2 / a1≤1. For example, the value of a1 / A can be 0.14, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, or a range consisting of any two values ​​therebetween. For example, the value of a2 / a1 can be 0.3, 0.4, 0.54, 0.6, 0.7, 0.8, 0.9, 1, or a range consisting of any two values ​​therebetween. Without being limited to any theory, the inventors of the present application have found that when the value of a1 / A is too small (for example, less than 0.14), the cycle performance of the electrochemical device is not significantly improved; when the value of a1 / A is too large (for example, greater than 0.55), the specific capacity of the electrochemical device will be affected. By regulating the value of a1 / A within the above range, it is beneficial to improve the cycle performance and specific capacity of the electrochemical device. By regulating the value of a2 / a1 within the above range, it is also beneficial to improve the cycle performance and specific capacity of the electrochemical device. The present application has no particular limitation on the value of a2%, as long as the purpose of the present application can be achieved. For example, a2% is 0.03% to 2%.

[0038] In some embodiments of the present application, the positive electrode active material also includes an M2 element, and the M2 element includes at least one of Fe, Cu, Cr or Zn. Based on the molar number of the Mn element, the molar content of the M2 element is b1%, satisfying 0.1<a1+b1≤2.05. For example, the value of a1+b1 can be 0.11, 0.5, 1, 1.5, 2, 2.05 or a range consisting of any two values ​​therebetween. Without being limited to any theory, the inventors of the present application have found that when the value of a1+b1 is too large (for example, greater than 2.05), the content of the M2 element also increases, which will affect the thermal stability of the positive electrode active material, thereby affecting the initial rate performance and cycle performance of the electrochemical device. By selecting the above-mentioned M2 element and regulating the value of the total molar content a1+b1 of the M1 element and the M2 element within the above range, it is beneficial to improve the cycle performance of the electrochemical device. The present application has no special restrictions on the value of b1, as long as the purpose of the present application can be achieved, for example, 0<b1≤0.05.

[0039] In some embodiments of the present application, the positive electrode active material also includes an M3 element, and the M3 element includes at least one of F, P, S or B. Based on the molar number of the Mn element, the molar content c1% of the M3 element is 0.1% to 2%. For example, the molar content c1% of the M3 element can be 0.1%, 0.5%, 1%, 1.5%, 2% or a range consisting of any two values ​​therebetween. Without being limited to any theory, the inventors of the present application have found that by selecting the above-mentioned M3 element, controlling the mass ratio of the boron-containing lithium salt to the positive electrode active material to be 0.0001 to 0.01, and regulating the molar content c1% of the M3 element within the above range, it is beneficial to form a structurally stable protective film to improve the manganese dissolution phenomenon of the positive electrode sheet, thereby improving the cycle performance of the electrochemical device.

[0040] In some embodiments of the present application, the electrochemical device satisfies at least one of the following characteristics: (iii) 0.1≤a1+c1≤4; (iv) the M3 element includes the F element, and the molar content of the F element is c2% based on the molar number of the Mn element, satisfying 0.05≤c2 / c1≤0.5. For example, the value of a1+c1 can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, or a range consisting of any two values ​​therebetween. For example, the value of c2 / c1 can be 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, or a range consisting of any two values ​​therebetween. Without being limited to any theory, the inventors of the present application have found that by regulating the value of a1+c1 and / or the value of c2 / c1 within the above range, it is beneficial to improve the cycle performance of the electrochemical device. The present application has no particular limitation on the value of c1%, as long as the purpose of the present application can be achieved, for example, 0.1≤c2≤1.

[0041] In some embodiments of the present application, the positive electrode active material comprises secondary particles, and the average particle size of the primary particles in the secondary particles is D1. In some embodiments of the present application, the Dv50 of the positive electrode active material is 4 μm to 15 μm. For example, the Dv50 of the positive electrode active material can be 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or a range consisting of any two values ​​therebetween.

[0042] In some embodiments of the present application, the average particle size D1 of the primary particles is 0.2 μm to 2 μm. For example, the average particle size D1 of the primary particles can be 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 1.5 μm, 2 μm, or a range consisting of any two values ​​therebetween. Without being limited to any theory, the inventors of the present application have found that by regulating the average particle size D1 of the primary particles within the above range, it is beneficial to improve the rate performance and cycle performance of the electrochemical device.

[0043] In some embodiments of the present application, 4≤Dv50 / D1≤50. The value of Dv50 / D1 can be 4, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 or a range consisting of any two values ​​therebetween. Without being limited to any theory, the inventors of the present application have found that by regulating the values ​​of Dv50 and Dv50 / D1 of the positive electrode active material within the above range, it is beneficial to improve the rate performance and cycle performance of the electrochemical device. In the present application, secondary particles refer to particles formed by agglomeration of primary particles.

[0044] In the present application, the Dv50 of the positive electrode active material can be measured by a laser particle size analyzer, and the average particle size of the primary particles can be measured by a scanning electron microscope.

[0045] In some embodiments of the present application, the electrolyte further includes a compound containing a sulfur-oxygen double bond, and the compound containing a sulfur-oxygen double bond includes at least one of 1,3-propane sultone (PS), propenyl-1,3-sultone (PTS) or vinyl sulfate (DTD). Based on the mass of the electrolyte, the mass percentage of the compound containing a sulfur-oxygen double bond is 0.01% to 2%. For example, the mass percentage of the compound containing a sulfur-oxygen double bond can be 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, or a range consisting of any two values ​​therebetween. Without being limited to any theory, the inventors of the present application have found that the presence of a compound containing a sulfur-oxygen double bond can slow down the increase in interfacial impedance of the electrochemical device during the cycle and improve the problem of decreased rate performance of the electrochemical device during the cycle. However, when the mass percentage of the compound containing a sulfur-oxygen double bond is too high (for example, higher than 2%), a thicker protective film will be formed at the negative electrode, which may cause problems such as lithium precipitation during high-rate charging. By selecting the above-mentioned compounds containing sulfur-oxygen double bonds and regulating their mass percentage content within the above-mentioned range, the initial rate performance and cycle performance of the electrochemical device are improved, while the DC resistance growth rate is reduced, thereby improving the problem of rate performance degradation during the cycle.

[0046] The present application has no particular restrictions on the preparation method of the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode active material may include but is not limited to the following steps: mixing the raw materials uniformly, calcining under a certain heating rate and controlling the ventilation volume, and the calcining temperature is T x , calcination time is t' y Then, the temperature is lowered at a certain rate to obtain the positive electrode active material. x and calcination time t' y There is no particular limitation, as long as the purpose of the present application can be achieved. For example, the heating rate is 5°C / min, and the calcination temperature Tx The calcination time is 800℃ to 900℃, t' y The temperature is 15 to 50 hours, and the cooling rate is 3°C / min. The present application has no particular restrictions on the above raw materials, as long as the purpose of the present application can be achieved. For example, the raw materials may include but are not limited to at least one of MnO2, Li2CO3, Al2O3 or Co2O3.

[0047] The heating rate, cooling rate, calcination time and calcination temperature usually affect the particle size of the positive electrode active material, the phase uniformity of metal and oxygen ions, the content of oxygen defects and other factors, and thus affect the physical and chemical properties of the positive electrode active material. For example, when the calcination temperature is reduced and / or the calcination time is shortened, the particle size of the positive electrode active material decreases; when the calcination temperature is increased and / or the calcination time is prolonged, the particle size of the positive electrode active material increases.

[0048] In the present application, there is no particular restriction on the method of introducing elements M1, M2 and M3 into the positive electrode active material, as long as the purpose of the present application can be achieved, for example, compounds containing M1, M2 and M3 are selectively added during the preparation of the positive electrode active material. The present application has no particular restriction on the compound containing M1, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of Nb2O5, MgO, TiO2, WO3, Ga2O3, ZrO2, Y2O3, V2O5, SrO2, MoO3, RuO2, AgO, SnO2, Au2O3, La2O3, CeO2, Pr2O3, Nd2O3, Sm2O3 or Gd2O3. The present application has no particular restriction on the compound containing M2, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of Fe2O3, CuO2, CrO3 or ZnO2. The present application has no particular limitation on the compound containing M3, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of LiF, HBO3, Li3PO4 or Li2SO4.

[0049] In the present application, the molar ratio of different elements in the positive electrode active material is calculated by disassembling an electrochemical device containing the positive electrode active material at a 0% charge state to obtain a positive electrode sheet, and then testing the contents of different elements.

[0050] The positive electrode sheet usually includes a positive current collector. In the present application, there is no special restriction on the positive current collector, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to aluminum foil, aluminum alloy foil or composite current collector. In the present application, there is no special restriction on the thickness of the positive current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 8μm to 12μm. In the present application, the positive electrode material layer can be arranged on one surface in the thickness direction of the positive current collector, or on two surfaces in the thickness direction of the positive current collector. It should be noted that the "surface" here can be the entire area of ​​the positive current collector or a partial area of ​​the positive current collector. There is no special restriction in the present application, as long as the purpose of the present application can be achieved.

[0051] In the present application, the positive electrode material layer includes the positive electrode active material in any of the aforementioned embodiments of the present application, and the positive electrode material layer may also include a binder. The present application has no particular limitation on the binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride.

[0052] In the present application, the positive electrode material layer may also include a conductive agent, and the present application has no particular restrictions on the conductive agent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials or conductive polymers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.

[0053] In the present application, the electrochemical device also includes a negative electrode sheet. There is no special limitation on the negative electrode sheet in the present application, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet usually includes a negative electrode collector and a negative electrode material layer. In the present application, the negative electrode material layer can be arranged on one surface in the thickness direction of the negative electrode collector, or on two surfaces in the thickness direction of the negative electrode collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode collector, or it can be a partial area of ​​the negative electrode collector. There is no special limitation in the present application, as long as the purpose of the present application can be achieved.

[0054] In the present application, there is no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or composite current collector, etc. In the present application, there is no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4 μm to 12 μm.

[0055] In the present application, the negative electrode material layer includes a negative electrode active material, wherein the negative electrode active material is not particularly limited as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of natural graphite, artificial graphite, intermediate phase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite or silicon oxide.

[0056] In the present application, the negative electrode material layer may further include a conductive agent. The present application has no particular limitation on the conductive agent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of the above conductive agents.

[0057] In the present application, the negative electrode material layer may further include a binder. The present application has no particular limitation on the binder, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of the above-mentioned binders.

[0058] Optionally, the negative electrode sheet may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a commonly used conductive layer in the art, and may include but is not limited to the above conductive agent and the above binder.

[0059] The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to polyethylene (PE), polypropylene (PP), polytetrafluoroethylene-based polyolefin (PO)-based membranes, polyester membranes (such as polyethylene terephthalate (PET) membranes), cellulose membranes, polyimide membranes (PI), polyamide membranes (PA), spandex, aramid membranes, woven membranes, non-woven membranes (non-woven fabrics), microporous membranes, composite membranes, diaphragm paper, rolled membranes or spun membranes, preferably PP. The isolation membrane of the present application may have a porous structure, and the size of the pore size is not particularly limited, as long as the purpose of the present application can be achieved, for example, the size of the pore size may be 0.01 μm to 1 μm.

[0060] For example, the isolation membrane may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may include but is not limited to at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance.

[0061] The inorganic layer may include, but is not limited to, inorganic particles and inorganic layer binders. The present application has no particular restrictions on inorganic particles. For example, it may include, but is not limited to, at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on inorganic layer binders. For example, it may include, but is not limited to, at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer may include, but is not limited to, at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).

[0062] In the present application, the electrolyte may further include a lithium salt, and the present application has no particular limitation on the lithium salt, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of LiPF6, LiClO4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2 or LiC(SO2CF3)3. Preferably, the lithium salt includes LiPF6.

[0063] In the present application, the electrolyte may also include a non-aqueous solvent, and the present application has no particular restrictions on the non-aqueous solvent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of a carbonate compound or a carboxylate compound. The above-mentioned carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The above-mentioned cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, or γ-butyrolactone.

[0064] The electrochemical device of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In some embodiments, the electrochemical device may include, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery, etc.

[0065] The preparation process of the electrochemical device is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device; or, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then placing the electrode assembly with the entire stacked structure in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed on the packaging bag as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.

[0066] The second aspect of the present application provides an electronic device, comprising the electrochemical device in any of the aforementioned embodiments of the present application. The electrochemical device provided by the present application has good cycle performance and rate performance, so that the electronic device provided by the present application has a long service life and good performance.

[0067] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, or a large household battery, etc.

[0068] Example

[0069] Test methods and equipment:

[0070] Rate performance test:

[0071] In an environment of 25°C, the lithium-ion battery is charged at a constant current of 0.5C to a voltage of 4.22V, then charged at a constant voltage to a current of 0.02C, left to stand for 60 minutes, and then discharged at a constant current of 0.2C to a voltage of 2.8V, and the discharge capacity is recorded as D0. After standing for 5 minutes, the lithium-ion battery is charged at a constant current of 0.5C to a voltage of 4.22V, then charged at a constant voltage to a current of 0.02C, left to stand for 60 minutes, and then discharged at a constant current of 5C to a voltage of 2.8V, and the discharge capacity is recorded as D'. Capacity retention rate = D' / D0×100%. The initial rate performance of the lithium-ion battery is the rate performance data tested when the number of cycles of the lithium-ion battery is less than 10.

[0072] Cycle performance test:

[0073] In an environment of 25°C, the lithium-ion battery was charged at a constant current of 1C to a voltage of 4.22V, then charged at a constant voltage to a current of 0.02C, left to stand for 60 minutes, and then discharged at a constant current of 1C to a voltage of 2.8V, and the discharge capacity D3 was recorded. After 500 cycles, the discharge capacity D4 was recorded, and the cycle capacity retention rate = D4 / D3×100%.

[0074] DC resistance (Rcc) test:

[0075] The lithium-ion battery was placed in an environment of 25°C for 5 minutes, then charged at a constant current rate of 0.5C to a voltage of 4.2V, charged at a constant voltage of 4.2V to a current of 0.025C, placed for 5 minutes, and then discharged at a rate of 0.2C to a voltage of 2.8V. The discharge capacity at this time was recorded as the actual capacity of the lithium-ion battery. The following test calculates the rate based on this actual capacity.

[0076] Then let the lithium-ion battery stand for 5 minutes in an environment of 25°C, charge it at a constant current of 0.5C to a voltage of 4.2V, charge it at a constant voltage of 4.2V to a current of 0.025C, and let it stand for 120 minutes. The state of charge of the lithium-ion battery is 100%. Then discharge it at a rate of 0.1C for 10 seconds, record the discharge current I1 and the voltage V1 after discharge, and the sampling interval of the voltage, current and time during this period is 100 milliseconds; then discharge the lithium-ion battery at a rate of 1C for 360 seconds, record the discharge current I2 and the voltage V2 at 1 second of discharge, and the sampling interval of the voltage, current and time during this period is 100 milliseconds. Calculate the DC resistance of the lithium-ion battery R = (V1-V2) / (I2-I1) by the following formula.

[0077] The DC resistance R measured when the battery state of charge is 50% before the cycle is recorded as R1, and the DC resistance R measured when the battery state of charge is 50% after 500 cycles is recorded as R2. The DC resistance growth rate = R2 / R1×100%.

[0078] Particle size test:

[0079] Add 0.02g of the material to be tested into a 50mL clean beaker, then add 20mL of deionized water, and then add a few drops of 1% surfactant sodium hexametaphosphate to completely disperse the powder in the water, ultrasonicate it in a 120W ultrasonic cleaner for 5 minutes, and use MasterSizer 2000 to test the particle size distribution. Dv50 is the cumulative 50% particle size in the volume reference distribution obtained by the laser scattering particle size analyzer. The average particle size D1 of the primary particles is obtained by scanning electron microscopy.

[0080] Example 1-1

[0081] <Preparation of positive electrode active material>

[0082] The raw materials MnO2, Li2CO3, Al2O3 and Co3O4 were mixed according to the molar ratio of Li, Mn, Al and Co elements of 1:1.96:0.03:0.01, and the calcination temperature was set to T x is 830℃, calcination time t' y The positive electrode active material LiMn with secondary particle morphology containing primary particle agglomeration was obtained for 35h. 1.96 Al 0.03 Co 0.01O4. Among them, the Dv50 of the MnO2 secondary particles is 11.8μm, the Dv50 of the positive electrode active material is 12.4μm, and the average particle size D1 of the primary particles is 0.6μm.

[0083] <Preparation of positive electrode sheet>

[0084] The positive electrode active material, conductive agent acetylene black, and binder polyvinylidene fluoride prepared above are mixed in a mass ratio of 96.5:2:1.5, and N-methylpyrrolidone (NMP) is added. The system is stirred under the action of a vacuum mixer until it becomes a uniform positive electrode slurry, wherein the solid content of the positive electrode slurry is 70%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and the aluminum foil is dried at 120°C for 1h to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides, and the single-sided coating mass of the positive electrode material layer is 20mg / cm 2 Then, after cold pressing, cutting, slitting, and welding the pole lugs, it was dried under vacuum conditions at 120°C for 1 hour to obtain a positive electrode sheet with a specification of 74mm×867mm.

[0085] <Preparation of negative electrode sheet>

[0086] The negative electrode active materials artificial graphite, styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) are mixed in a mass ratio of 96:2:2, and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer, wherein the solid content of the negative electrode slurry is 75%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12 μm, and the copper foil is dried at 120°C to obtain a negative electrode sheet with a coating thickness of 130 μm and a negative electrode material layer coated on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides, and the single-sided coating mass of the negative electrode material layer is 6.5 mg / cm 2 Then, after cold pressing, cutting, slitting, and welding the pole lugs, it was dried under vacuum conditions at 120°C for 1 hour to obtain a negative electrode sheet with a specification of 78mm×875mm.

[0087] <Preparation of Electrolyte>

[0088] In a dry argon atmosphere glove box, PC, EC, and DEC were mixed in a mass ratio of 1:1:1, and then lithium salt LiPF6 and boron-containing lithium salt LiBF4 were added to an organic solvent to dissolve and mix evenly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the content of LiPF6 in the electrolyte is 12.5%. The mass ratio of LiBF4 to the mass of the positive electrode active material is shown in the following table.

[0089] <Preparation of Separator Film>

[0090] A porous PE film with a thickness of 7 μm (provided by Celgard Company) was used.

[0091] <Preparation of lithium-ion batteries>

[0092] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and the electrode assembly is wound. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the electrolyte is injected after drying. The lithium-ion battery is obtained through vacuum packaging, standing, formation, degassing, trimming and other processes. Among them, the injection amount of the electrolyte is controlled to be 4.2g / Ah, and the mass ratio of the boron-containing lithium salt to the positive electrode active material is 0.002; the formation upper limit voltage is 4.15V, the formation temperature is 70°C, and the formation standing time is 2h.

[0093] Embodiment 1-2 to Embodiment 1-10, Embodiment 1-19

[0094] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0095] Example 1-11 to Example 1-18

[0096] Except for adjusting the molar ratio of the raw materials according to the molar ratio of different elements in the positive electrode active material in <Preparation of Positive Electrode Active Material> and adjusting the mass percentage of the boron-containing lithium salt and the mass ratio of the boron-containing lithium salt to the positive electrode active material as shown in Table 1, the rest is the same as Example 1-1.

[0097] Example 2-1 to Example 2-7

[0098] In <Preparation of Positive Electrode Active Material>, except that the compound containing M1 is added as a raw material according to Table 2 and the molar ratio of the raw materials is adjusted according to the molar ratio of different elements in the positive electrode active material, the rest is the same as Example 1-5.

[0099] Example 2-8 and Example 2-9

[0100] In <Preparation of Positive Electrode Active Material>, except that the compound containing M1 and the compound containing M2 are added as raw materials according to Table 2 and the molar ratio of the raw materials is adjusted according to the molar ratio of different elements in the positive electrode active material, the rest is the same as Examples 1-5.

[0101] Example 2-10 and Example 2-11

[0102] In <Preparation of Positive Electrode Active Material>, except that the compound containing M3 is added as a raw material according to Table 3 and the molar ratio of the raw materials is adjusted according to the molar ratio of different elements in the positive electrode active material, the rest is the same as Example 1-5.

[0103] Example 2-12 to Example 2-15

[0104] In <Preparation of Positive Electrode Active Material>, except that the compound containing M3 is added as a raw material according to Table 3 and the molar ratio of the raw materials is adjusted according to the molar ratio of different elements in the positive electrode active material, the rest is the same as Example 2-1.

[0105] Example 2-16

[0106] In <Preparation of Positive Electrode Active Material>, except that the compound containing M2 and the compound containing M3 are added as raw materials according to Table 3, and the molar ratio of the raw materials is adjusted according to the molar ratio of different elements in the positive electrode active material, the rest is the same as Example 2-1.

[0107] In Examples 3-1 to 3-5, except for adjusting the relevant preparation parameters according to Table 4, the rest are the same as Examples 1-5.

[0108] In Examples 4-1 to 4-6, except that a compound containing a sulfur-oxygen double bond is added in <Preparation of Electrolyte> and relevant preparation parameters are adjusted according to Table 5, the rest are the same as Examples 1-5.

[0109] In Comparative Examples 1-1 to Comparative Examples 1-4, except for adjusting the relevant preparation parameters according to Table 1 or adjusting the molar ratio of the raw materials according to the molar ratio of different elements in the positive electrode active material, the rest is the same as Example 1-1.

[0110] The preparation parameters and properties of each embodiment and each comparative example are shown in Tables 1 to 5.

[0111] Table 1

[0112]

[0113]

[0114] Note: “ / ” in Table 1 indicates that there is no corresponding preparation parameter or substance.

[0115] It can be seen from Examples 1-1 to 1-18 and Comparative Examples 1-1 to 1-4 that when the value of the molar ratio A of the X element and the Mn element and the mass ratio of the boron-containing lithium salt to the positive electrode active material are within the scope of the present application, the obtained electrochemical device has good initial rate performance and cycle performance, as well as a lower Rcc growth rate. It can be seen from Examples 1-1 to 1-19 that when the mass percentage of the boron-containing lithium salt is within the scope of the present application, the obtained electrochemical device has better comprehensive performance. This shows that the electrochemical device provided by the present application can simultaneously improve the rate performance and cycle performance of the electrochemical device and reduce the Rcc growth rate under the synergistic effect of the positive electrode active material and the electrolyte.

[0116] Table 2

[0117]

[0118] Note: “ / ” in Table 2 indicates that there is no corresponding preparation parameter or substance.

[0119] The introduction of M1 elements and / or M2 elements into the positive electrode active material usually affects the performance of the electrochemical device, such as rate performance, cycle performance and Rcc growth rate. It can be seen from Examples 1-5, 2-1 to 2-7 that the introduction of M1 elements into the positive electrode active material can further improve the initial rate performance and cycle performance of the electrochemical device and reduce the Rcc growth rate. It can be seen from Examples 2-1 to 2-7 that when the values ​​of a1, a2 / a1, and a1 / A are within the scope of the present application, the obtained electrochemical device has better initial rate performance and cycle performance, as well as a lower Rcc growth rate. It can be seen from Examples 1-5, 2-8 and 2-9 that the simultaneous introduction of M1 elements and M2 elements into the positive electrode active material can further improve the initial rate performance and cycle performance of the electrochemical device and reduce the Rcc growth rate. It can be seen from Examples 2-8 and 2-9 that when the value of a1+b1 is within the scope of the present application, the obtained electrochemical device has good initial rate performance and cycle performance, as well as a lower Rcc growth rate.

[0120] Table 3

[0121]

[0122] Note: “ / ” in Table 3 indicates that there is no corresponding preparation parameter or substance.

[0123] The introduction of at least one of the M1 element, the M2 element or the M3 element into the positive electrode active material generally affects the performance of the electrochemical device, such as the initial rate performance, the cycle performance and the Rcc growth rate. It can be seen from Examples 1-5, 2-10 and 2-11 that the introduction of the M3 element into the positive electrode active material can further improve the initial rate performance and the cycle performance of the electrochemical device and reduce the Rcc growth rate. It can be seen from Examples 1-5, 2-12 to 2-15 that the simultaneous introduction of the M1 element and the M3 element into the positive electrode active material can further improve the initial rate performance and the cycle performance of the electrochemical device and reduce the Rcc growth rate. It can be seen from Examples 2-10 to 2-15 that when the value of at least one of c1, c2 / c1 or a1+c1 is within the scope of the present application, the obtained electrochemical device has good initial rate performance and cycle performance, as well as a lower Rcc growth rate. It can be seen from Examples 1-5 and Examples 2-16 that when the M1 element, the M2 element and the M3 element are simultaneously introduced into the positive electrode active material, the initial rate performance and the cycle performance of the electrochemical device can be further improved and the Rcc growth rate can be reduced.

[0124] Table 4

[0125]

[0126] The particle size of primary particles and positive electrode active materials usually affects the performance of electrochemical devices, such as rate performance, cycle performance and Rcc growth rate. It can be seen from Examples 1-5 and Examples 3-1 to 3-5 that when the particle size of primary particles and positive electrode active materials is within the range of this application, that is, the average particle size D1 of primary particles, Dv50 of positive electrode active materials and Dv50 / D1 values ​​are within the range of this application, the obtained electrochemical device has good comprehensive performance.

[0127] Table 5

[0128]

[0129] Note: “ / ” in Table 5 indicates that there is no corresponding preparation parameter or substance.

[0130] Adding a compound containing a sulfur-oxygen double bond to an electrolyte usually affects the performance of an electrochemical device, such as rate performance, cycle performance, and Rcc growth rate. It can be seen from Examples 1-5, 4-1, and 4-6 that adding a compound containing a sulfur-oxygen double bond to an electrolyte can further improve the rate performance and cycle performance of an electrochemical device and reduce the Rcc growth rate; when the mass percentage of the compound containing a sulfur-oxygen double bond is within the scope of this application, the obtained electrochemical device has good rate performance and cycle performance, as well as a lower Rcc growth rate.

[0131] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrochemical device comprising a positive electrode sheet and an electrolyte, wherein: The positive electrode plate includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes Mn element and X element, the X element includes at least one of Co element or Al element, the molar ratio of the X element to the Mn element is A%, A is 0.1 to 10, the positive electrode active material also includes M2 element, the M2 element includes at least one of Fe, Cu, Cr or Zn; the electrolyte includes a boron-containing lithium salt, wherein the boron-containing lithium salt includes at least one of lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium dioxalatoborate or lithium tetraborate, and the mass ratio of the boron-containing lithium salt to the positive electrode active material is 0.0001 to 0.

01.

2. The electrochemical device according to claim 1, wherein: Based on the mass of the electrolyte, the mass percentage of the boron-containing lithium salt is 0.01% to 2.2%.

3. The electrochemical device according to claim 1, wherein The positive electrode active material also includes an M1 element, and the M1 element includes at least one of Nb, Mg, Ti, W, Ga, Zr, Y, V, Sr, Mo, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm or Gd, and the molar content a1% of the M1 element is 0.1% to 2% based on the molar number of the Mn element.

4. The electrochemical device according to claim 3, which satisfies at least one of the following characteristics: (i) 0.14≤a1 / A≤0.55; (ii) The M1 element includes Nb element, and the molar content of Nb element is a2% based on the molar number of the Mn element, satisfying 0.3≤a2 / a1≤1.

5. The electrochemical device according to claim 1, wherein The positive electrode active material also includes an M1 element, and the M1 element includes at least one of Nb, Mg, Ti, W, Ga, Zr, Y, V, Sr, Mo, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm or Gd. Based on the molar number of the Mn element, the molar content of the M1 element is a1%, and the molar content of the M2 element is b1%, satisfying 0.1<a1+b1≤2.

05.

6. The electrochemical device according to claim 1, wherein The positive electrode active material further includes an M3 element, the M3 element includes at least one of F, P, S or B, and a molar content c1% of the M3 element is 0.1% to 2% based on the mole number of the Mn element.

7. The electrochemical device according to claim 6, wherein: The positive electrode active material further includes an M1 element, and the M1 element includes at least one of Nb, Mg, Ti, W, Ga, Zr, Y, V, Sr, Mo, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm or Gd, and the molar content of the M1 element is a1% based on the molar number of the Mn element, which satisfies at least one of the following characteristics: (iii) 0.1≤a1+c1≤4; (iv) The M3 element includes the F element, and the molar content of the F element is c2% based on the molar number of the Mn element, satisfying 0.05≤c2 / c1≤0.

5.

8. The electrochemical device according to claim 1, wherein The positive electrode active material comprises secondary particles, the average particle size of primary particles in the secondary particles is D1, and the secondary particles satisfy at least one of the following characteristics: (1) The Dv50 of the positive electrode active material is 4 μm to 15 μm; (2) The average particle size D1 of the primary particles is 0.2 μm to 2 μm; (3) 4≤Dv50 / D1≤50, where Dv50 is the particle size of 50% cumulative in the volume reference distribution of the positive electrode active material measured by a laser scattering particle size analyzer.

9. The electrochemical device according to claim 1, wherein: The electrolyte also includes a compound containing a sulfur-oxygen double bond, wherein the compound containing a sulfur-oxygen double bond includes at least one of 1,3-propane sultone, propenyl-1,3-sultone or vinyl sulfate. Based on the mass of the electrolyte, the mass percentage of the compound containing a sulfur-oxygen double bond is 0.01% to 2%.

10. An electronic device comprising the electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for producing lithium manganate particle powder and nonaqueous electrolyte secondary battery

    CN102149641A

  • Nonaqueous electrolyte secondary battery

    JP2000138063A